Streptomycin resistance in Clavibacter michiganensis subsp. michiganensis strains from Chile is related to an rpsL gene mutation. (26th December 2018) - Valenzuela, M.; Méndez, V.; Montenegro, I.; Besoain, X.; Seeger, M.
Abstract : Streptomycin has been used for decades in Chile to control Clavibacter michiganensis subsp. michiganensis (Cmm), the causal agent of tomato bacterial canker. The aim of this work was to evaluate streptomycin resistance and to analyse the presence of resistance‐related genes in Cmm strains from Chile. A collection of 25 Cmm strains isolated from different localities in central Chile between 1996 and 2015 was analysed. Minimum inhibitory concentration (MIC) of streptomycin was determined. A search of streptomycin resistance‐related genes was carried out in Cmm genomes, and the presence of these genes was studied in all Chilean strains using PCR and sequencing techniques. MIC results showed that four of 25 strains were highly sensitive to streptomycin, with MIC values <2 μg mL −1 . The remaining 21 strains possessed MIC of streptomycin ≥100 μg mL −1 . The strB gene, encoding an aminoglycoside 6‐phosphotransferase that inactivates streptomycin, was detected in all Chilean strains, including sensitive and resistant strains. In the 21 resistant strains, a mutation in codon 43 of the rpsL gene was determined, conferring high streptomycin resistance. Interestingly, the four streptomycin‐sensitive Cmm strains did not possess this mutation. This study proposes that the continuous use of streptomycin leads to emergence of resistant Cmm strains, challenging researchers to look for novel alternatives to control this plant pathogenic bacterium.